2018
DOI: 10.18433/jpps29659
|View full text |Cite
|
Sign up to set email alerts
|

PAMAM-dendrimer Enhanced Antibacterial Effect of Vancomycin Hydrochloride Against Gram-Negative Bacteria

Abstract: Purpose: The antibacterial activity of some antibiotics is specific to either Gram-positive or Gram-negative bacteria.  There are different mechanisms behind such insensitivities like inability of antibiotics to permeate through some bacterial membranes, as is the case for vancomycin in Gram-negative bacteria. The present investigation tries to overcome this problem by dendrimers, in order to make Gram-negative bacteria responsive to vancomycin. Methods: The effects of generations 3 (G3) and 5 (G5) polyamidoam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…It is known that antibacterial properties of nanoparticles (both dendrimers and silver NPs) strongly depend on their structure, charge, size, and adsorption ability at the bacterial surface (Felczak et al, 2012; Le Ouay and Stellacci, 2015; Tang and Zheng, 2018). As potential membrane permeabilizers, the dendronized nanoparticles may also enhance the antibacterial effect of antibiotics or antimicrobial proteins, especially against gram-negative bacteria (Winnicka et al, 2013; Serri et al, 2019). Our recent work showed that poly(propylene) imine glycodendrimers improved the antimicrobial properties of phage KP27 endolysin against P. aeruginosa cells (Ciepluch et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that antibacterial properties of nanoparticles (both dendrimers and silver NPs) strongly depend on their structure, charge, size, and adsorption ability at the bacterial surface (Felczak et al, 2012; Le Ouay and Stellacci, 2015; Tang and Zheng, 2018). As potential membrane permeabilizers, the dendronized nanoparticles may also enhance the antibacterial effect of antibiotics or antimicrobial proteins, especially against gram-negative bacteria (Winnicka et al, 2013; Serri et al, 2019). Our recent work showed that poly(propylene) imine glycodendrimers improved the antimicrobial properties of phage KP27 endolysin against P. aeruginosa cells (Ciepluch et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The viscosity of the gel was determined by Brookfield LV Viscometer [29]. The prepared quercetin loaded nanosponges gel of 5g was taken in a beaker and by selecting spindle number 64 the viscosity of the gel was noted.…”
Section: Viscositymentioning
confidence: 99%
“…10 mg of the gel was placed in 10 ml of phosphate buffer of pH 7.4 and the solution was kept aside for 24h and the solution was stirred on a magnetic stirrer (Remi equipment, Mumbai) for 30 min and filtered [29]. The absorbance of a filtered solution was measured by using a UV spectrophotometer (Shimadzu, Japan) at 372 nm.…”
Section: Percentage Of Drug Contentmentioning
confidence: 99%
“…The higher local concentration of AMP allows a multivalent binding and enhances the destabilizing effect of the bacterial membrane. Dendrimers may also be used in the rapid diagnosis to discern between Gram-negative or Gram-positive bacteria, through a pH-dependent bacteria-selective aggregation occurring within 5 min of adding the dendrimer to a bacterial suspension [ 113 ]; and as carriers of different drugs such as vancomycin or agents like LED209, both specific to Gram-negative microorganisms [ 114 , 115 ].…”
Section: Dendrimers and Dendritic Materials In The Prevention Trementioning
confidence: 99%